A Unique Case of Primary Ewing's Sarcoma of the Cervical Spine in a 53-Year-Old Male: A Case Report and Review of the Literature. (23rd February 2015) - Holland, Marshall T.; Flouty, Oliver E.; Close, Liesl N.; Reddy, Chandan G.; Howard, Matthew A.
Abstract : Extraskeletal Ewing's sarcoma (EES) is a rare presentation, representing only 15% of all primary Ewing's sarcoma cases. Even more uncommon is EES presenting as a primary focus in the spinal canal. These rapidly growing tumors often present with focal neurological symptoms of myelopathy or radiculopathy. There are no classic characteristic imaging findings and thus the physician must keep a high index of clinical suspicion. Diagnosis can only be definitively made by histopathological studies. In this report, we discuss a primary cervical spine EES in a 53-year-old man who presented with a two-month history of left upper extremity pain and acute onset of weakness. Imaging revealed a cervical spinal canal mass. After undergoing cervical decompression, histopathological examination confirmed a diagnosis of Ewing's sarcoma. A literature search revealed fewer than 25 reported cases of primary cervical spine EES published in the past 15 years and only one report demonstrating this pathology in a patient older than 30 years of ageage = 38 . Given the low incidence of this pathology presenting in this age group and the lack of treatment guidelines, each patient's plan should be considered on a case-by-case basis until further studies are performed to determine optimal evidence based treatment.